Prevalence and clinical markers of herpes simplex virus infection in oral lesions of bullous pemphigoid - Zhang, Hanmei; Yu, Meiwen; Liang, Guirong; Li, Suo; Zhao, Chenjing; Jing, Ke; Feng, Suying (Frontiers in Immunology, 2024)
Background: The manifestations of bullous pemphigoid (BP) and herpes simplex virus (HSV) infection are similar in oral mucosa and the laboratory detection of HSV has some limitations, making it difficult to identify the HSV infection in oral lesions of BP. Besides, the treatments for BP and HSV infection have contradictory aspects. Thus, it is important to identify the HSV infection in BP patients in time. Objective: To identify the prevalence and clinical markers of HSV infection in oral lesions of BP. Methods: This prospective cross-sectional descriptive analytical study was conducted on 42 BP patients with oral lesions. Thirty-two BP patients without oral lesions and 41 healthy individuals were enrolled as control groups. Polymerase chain reaction was used to detect HSV. Clinical and laboratory characteristics of patients with HSV infection were compared with those without infection. Results: Nineteen (45.2%) BP patients with oral lesions, none (0.0%) BP patients without oral lesions and 4 (9.8%) healthy individuals were positive for HSV on oral mucosa. Among BP patients with oral lesions, the inconsistent activity between oral and skin lesions (p=0.001), absence of blister/blood blister in oral lesions (p=0.020), pain for oral lesions (p=0.014) were more often seen in HSV-positive than HSV-negative BP patients; the dosage of glucocorticoid (p=0.023) and the accumulated glucocorticoid dosage in the last 2 weeks (two-week AGC dosage) (p=0.018) were higher in HSV-positive BP patients. Combining the above 5 variables as test variable, the AUC was 0.898 (p<0.001) with HSV infection as state variable in ROC analysis. The absence of blister/blood blister in oral lesions (p=0.030) and pain for oral lesions (p=0.038) were found to be independent predictors of HSV infection in multivariable analysis. Fourteen (73.7%) HSV-positive BP patients were treated with two-week famciclovir and the oral mucosa BPDAI scores significantly decreased (p<0.001). Conclusions: HSV infection is common in BP oral lesions. The inconsistent activity between oral and skin lesions, absence of blister in oral lesions, pain for oral lesions, higher currently used glucocorticoid dosage and higher two-week AGC dosage in BP patients should alert physicians to HSV infection in oral lesions and treat them with two-week famciclovir in time.